THE INFANT WITH CYANOSIS IN THE EMERGENCY ROOM - Valeriu Popescu (Amaltea Medical Publishing House, 2008)
The infant with cyanosis is a distressing medical presentation. This article provides an overview of the many causes of cyanosis. Emphasis is placed on the pathophysiology of each disease process: cardiac system - the most commonly involved organ system; pulmonary system; upper airway obstruction; infectious processes in the context of septic shock, meningitis, or pulmonary disease; shock (hypovolemic, distributive, cardiogenic); gastroesophageal reflux; neurologic system; sudden infant death syndrome and near-miss sudden infant death syndrome; trauma; poisoning; metabolic disturbances; methemoglobinemia. A rational approach to diagnosis is outlined